Lipids in oocytes of ants Neoponera villosa (Hymenoptera: Ponerinae) - Caperucci, Débora [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (My University, 2006)
Elements of oocyte of Neoponera villosa ants (workers and queen) were analyzed histochemically and ultrastructurally. It was observed that lipids are the first element to be deposited. They appear in oocytes of all stages. Lipids probably arose in the younger oocytes (stages I and II) from mitochondria of their own cytoplasm and from the nurse cells as well. In mature oocytes (stage III) the cells of the follicular epithelium appears with droplets of lipids in their cytoplasm showing that besides the other sites, this epithelium can also be active in lipid synthesis.
Keywords: Ants; Lipid; Neoponera villosa; Ovaries; Formicidae; Hymenoptera; Ponerinae